PENGARUH LINGKUNGAN FISIK TERHADAP TERJADINYA STRESS KERJA PADA PEKERJA INDUSTRI BENGKEL LAS DI KOTA PEKANBARU - Kursiah Warti Ningsih; Rahmi Pramulia Fitri (LPPM Universitas Abdurrab, 2017)
Stressisan inevitable consequence of modern life. Job stress can be define dasaphysical and mental responses that occurwhenthe demand/job requirements do notmatch the capabilities, resources orneeds ofthe worker. Based on theresults ofthe initial survey conducted by researchersin May 2016, thatintheworkshopthere isa riskof physicalwork environmenthazardssuch astemperature, lightingandnoisecoming fromthe equipment. Thistypeof researchdesignisAnalyticcross sectional study, witha samplesizeof65peopleworkingin thewelding shopPekanbaru. Sampling was done bypurposive sampling. Data analysis was performedusing univariate, bivariatechi-squaretest, and multivaria telogistic regression. The result showed that the variables that significantly influencethe works tessis temperature (OR = 22.36), lighthing (OR =13.51), noise (OR =2.04) and age(OR =1.85). This study found 33 of 65 respondent sex periencing work stress (50.8%). Variable related tojob stress are work experience, hours worked, age, use of PPE, noise, temperature and lighting. Variables that have a significant impactis the temperature, lighting, noise, age. The most dominant variableis the temperature (OR: 22.36). Should be applied to the management of stress on workers' so stresscan be overcome. Keyword : Job stress, welding shop, the physicalenvironment